2020
DOI: 10.35371/aoem.2020.32.e16
|View full text |Cite
|
Sign up to set email alerts
|

A study of job stress, suicidal ideation and suicide attempts in display manufacturing workers: a cross-sectional study

Abstract: Background This study aimed to investigate the association between job stress and suicide ideation/attempts among display manufacturing workers. Methods Data were collected from 836 workers in a display manufacturing company who participated in health screenings from May 22 to June 16, 2017. The data included general characteristics, night work, job tenure, previous physician-diagnosed chronic diseases, suicidal ideation/suicide attempts, and job stress. We investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…This confirms the first research hypothesis. These results are consistent with the results of previous studies, showing the positive associations between general work stress and suicide cognition (74)(75)(76). Considerable job-related stress and are more prone to exhibit a variety of psychological disorders, such as PTSD and suicidal thoughts (77).…”
Section: Discussionsupporting
confidence: 93%
“…This confirms the first research hypothesis. These results are consistent with the results of previous studies, showing the positive associations between general work stress and suicide cognition (74)(75)(76). Considerable job-related stress and are more prone to exhibit a variety of psychological disorders, such as PTSD and suicidal thoughts (77).…”
Section: Discussionsupporting
confidence: 93%
“…But in cases of men workers, depression rather than job stress correlated with experiences of suicidal ideation/attempt. (20) Among medical residents, burnout is a common phenomenon due to overburden of work. (21) The study also showed that 64.05% of interns, 40% of junior residents show burnout thoughts.…”
Section: Discussionmentioning
confidence: 99%
“… 32 Alcohol intake was classified as “people who do not drink,” “those who drink one to two times a week,” and “those who drink more than three times a week.” Smoking was classified as “current smokers,” “past smokers,” and “non-smokers.” Exercise was classified as “those who perform no exercise,” “those who exercise one to two times a week,” and “those who exercise more than three times a week.” Shift work was classified into “those who have work shifts” and “those who do not have work shifts”. 33 Tenure was classified as ‘less than 5 years,’ ‘more than 5 years and less than 10 years,’ ‘more than 10 years and less than 15 years,’ and ‘more than 15 years.’ Hypertension was defined as systolic blood pressure of 140 mmHg or higher, diastolic blood pressure of 90 mmHg or higher, or taking high blood pressure drugs according to guidelines of the Korea Hypertension Association in 2018. 34 Dyslipidemia was defined as total cholesterol of 240 mg/dL or more, a neutral fat of 200 mg/dL or more, a high-density cholesterol of 40 mg/dL or a low-density cholesterol of 160 mg/dL or more, or taking a dyslipidemia drug.…”
Section: Methodsmentioning
confidence: 99%